Determinants of CEO Pay: A Comparison of ExecuComp and Non-ExecuComp Firms - Cadman, Brian; Klasa, Sandy; Matsunaga, Steve (The Accounting Review, 2010)
ABSTRACT: We document that firms included in the ExecuComp database tend to be larger, more complex, followed by more analysts, have greater stock liquidity levels, and have higher total, but less concentrated, institutional ownership than other firms. Based on these differences, we test and find support for three predictions. First, ExecuComp firms rely more heavily on earnings and stock returns in determining CEO cash compensation. Second, the weight on earnings is more sensitive to differences in the extent of growth opportunities for ExecuComp firms. Third, the positive relation between institutional ownership concentration and the value of stock option grants is stronger for ExecuComp firms. Overall, our results suggest that ExecuComp and non-ExecuComp firms operate in different contracting environments that lead to differences in the design of their executive compensation contracts. As a result, care should be taken in extending results based on ExecuComp samples to non-ExecuComp firms.